Last of the tsars : Nicholas II and the Russian Revolution - Service, Robert (London Macmillan, 2017)
In March 1917, Nicholas II, the last Tsar of All the Russias, abdicated and the dynasty that had ruled an empire for three hundred years was forced from power by revolution. Now, on the hundredth anniversary of that revolution, Robert Service, the eminent historian of Russia, examines Nicholas's reign in the year before his abdication and the months between that momentous date and his death, with his family, in Ekaterinburg in July 1918. The story has been told many times, but Service's profound understanding of the period and his forensic examination of hitherto untapped sources, including the Tsar's diaries and recorded conversations, shed remarkable new light on his reign, also revealing the kind of ruler Nicholas believed himself to have been, contrary to the disastrous reality. The Last of the Tsars is a masterful study of a man who was almost entirely out of his depth, perhaps even willfully so. It is also a compelling account of the social, economic and political foment in Russia in the aftermath of Alexander Kerensky's February Revolution, the Bolshevik seizure of power in October 1917 and the beginnings of Lenin's Soviet republic.
Keywords: Soviet Union; Kings and rulers; Government, Resistance to Revolution